Le dépouillement ou l’épreuve de l’étrange dans Field Study de Rachel Seiffert - Pascale Tollance (Études Britanniques Contemporaines, 2007)
Seiffert’s second book, a collection of eleven short stories, presents us page after page with characters coming face to face with the strange and the unknown, whether it comes from elsewhere, from nowhere, or whether it lives right there. But throughout these encounters, the strange is also the product of a terse and spare prose which strips things away to reveal their otherness. The main stranger here is the text itself, which, despite its apparent simplicity and smoothness, stands out as text whilst trying to achieve the impersonality and silence of photography or film. Like the characters, the reader is made to experience distance and separation. Like them, he is also given a chance to have a more uncluttered access to things. Experiencing strangeness means experiencing the resistance and opacity of a world that cannot be appropriated and the limit of one’s desire to know and understand oneself and others. It also means looking at things and words differently and finding in their materiality a silence through which they are never just themselves. The strange is then the unknown which makes things possible, the unknown which gives Seiffert’s intensely concrete language its poetic quality.